Regulation of antiviral and antitumor immunity by the BRCA1 pseudogene in human cancers - Yoo Jane Han; Jing Zhang; Maryam Shariff; Sulin Wu; Galina Khramtsova; Long Chi Nguyen; Daniel S. Peiffer; Nansheng Li; Anna Lewicka; Matthew Moore; Joseph A. Piccirilli; Olufunmilayo I. Olopade (Proceedings of the National Academy of Sciences, 2026)
Pseudogenes have been regarded as nonfunctional byproducts of evolutionary processes. However, emerging evidence indicates that pseudogenes perform diverse biological roles in human physiology and pathology. We identified the BRCA1 pseudogene ( BRCA1P1 ), a fusion pseudogene derived from the BRCA1 tumor suppressor and RPLP1 ribosomal protein genes, as an immunoregulatory RNA in breast cancer. In this study, we show that BRCA1P1 expression varies across multiple cancer cell types, with no significant association with BRCA1 or BRCA2 somatic mutations in breast and ovarian tumors. Interestingly, BRCA1P1 inhibition elicits antitumor effects in multiple cancer cell types and preclinical tumor models through an antiviral defense mechanism. Loss of BRCA1P1 induces antiviral gene expression, promotes apoptosis, and increases sensitivity to chemotherapy in various cancer cells, without inducing apoptosis in nonmalignant cells. This antiviral response also enhances macrophage-mediated phagocytosis of BRCA1P1 -deficient cancer cells. Mechanistically, the majority of BRCA1P1 transcripts are circular RNAs and regulate NF-κB-driven antiviral gene expression. Furthermore, intratumoral expression of BRCA1P1 is elevated in tumor cells, compared to normal breast tissue, and its depletion significantly inhibits the growth of both primary and metastatic breast tumor organoids. Finally, in a humanized mouse model of breast cancer, BRCA1P1 loss stimulates antiviral gene expression and increases T cell infiltration into tumors. These findings support a critical role for BRCA1P1 in regulating innate immune defense and antitumor responses across cancer types, suggesting that targeting pseudogene-derived RNAs may offer innovative therapeutic strategies to enhance antitumor immunity in breast and other cancers.